2021
DOI: 10.3389/fmars.2020.600836
|View full text |Cite
|
Sign up to set email alerts
|

Greater Mitochondrial Energy Production Provides Resistance to Ocean Acidification in “Winning” Hermatypic Corals

Abstract: Coral communities around the world are projected to be negatively affected by ocean acidification. Not all coral species will respond in the same manner to rising CO2 levels. Evidence from naturally acidified areas such as CO2 seeps have shown that although a few species are resistant to elevated CO2, most lack sufficient resistance resulting in their decline. This has led to the simple grouping of coral species into “winners” and “losers,” but the physiological traits supporting this ecological assessment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Although the drastic decline in calcification rates observed in the laboratory for the fast‐growing coral A. solitaryensis may be overestimated due to the high p CO 2 used in the OAW treatment during the incubation experiment performed in July 2016, the results obtained in the laboratory and field surveys both support the fact that colonization by fast‐growing species such as Acroporids will be limited by ocean acidification and only the slow‐growing coral species, such as Poritids which are already established at these latitudes, could persist under future ocean acidification. These results are similar to observations made under laboratory conditions (Brown & Edmunds, 2016) and at the tropical natural analogues for ocean acidification in Papua New Guinea, where Poritid corals are some of the few corals remaining in acidified areas (Fabricius et al, 2011) demonstrating physiological traits that could contribute to their resistance to OA (Agostini et al, 2021). No difference in the photosynthetic rates was observed for both species of corals between colonies transplanted at the ocean warming alone and the combined warming and acidification analogues.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although the drastic decline in calcification rates observed in the laboratory for the fast‐growing coral A. solitaryensis may be overestimated due to the high p CO 2 used in the OAW treatment during the incubation experiment performed in July 2016, the results obtained in the laboratory and field surveys both support the fact that colonization by fast‐growing species such as Acroporids will be limited by ocean acidification and only the slow‐growing coral species, such as Poritids which are already established at these latitudes, could persist under future ocean acidification. These results are similar to observations made under laboratory conditions (Brown & Edmunds, 2016) and at the tropical natural analogues for ocean acidification in Papua New Guinea, where Poritid corals are some of the few corals remaining in acidified areas (Fabricius et al, 2011) demonstrating physiological traits that could contribute to their resistance to OA (Agostini et al, 2021). No difference in the photosynthetic rates was observed for both species of corals between colonies transplanted at the ocean warming alone and the combined warming and acidification analogues.…”
Section: Discussionsupporting
confidence: 87%
“…We conducted field surveys to characterize the existing coral and kelp communities at these three locations and we carried out transplantation experiments of kelp (to assess herbivory) and of two hermatypic corals (to study their growth, photosystem efficiency and metabolic rates) at these natural analogues for future conditions. One of the coral species, Acropora solitaryensis , represents a fast‐growing, branching species that possesses complex morphology but is vulnerable to OA (Agostini et al, 2021) and has shown a rapid poleward expansion over the last few decades (Yamano et al, 2011). The other species, Porites heronensis , is a slow‐growing, encrusting species that provide relatively low complexity, although it is resistant to OA (Agostini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies to allocate energy toward skeletal or tissue growth are at the base of the different resistances of corals to acidification (Agostini et al, 2021). Models on tissue physiological processes indicate that, for corals, a thinner tissue layer favors a strong diffusion gradient between the coral epidermis and the water column (Jokiel, 2011; Jokiel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mesophotic corals and corals inhabiting naturally acidic areas share some similarities in their physiological traits and gene expression patterns. In fact, corals from both environments possess low tissue biomass (i.e., protein content per coral surface area), which in OA‐resistant species results in a higher potential for energy production (Agostini et al, 2021) and a higher flexibility in allocating energy toward skeletal growth (Agostini et al, 2021; Wall et al, 2017). Moreover, the regulation of the expression of carbonic anhydrases seems to be a crucial mechanism to control inorganic carbon concentrations within cells in both mesophotic corals and corals from naturally acidic areas (Kenkel et al, 2018; Malik et al, 2020; Teixidó et al, 2020).…”
Section: Introductionmentioning
confidence: 99%